2022
DOI: 10.1177/21501351221100791
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Arrest in Children Following Cardiac Surgery: A Scoping Review of Contributing Factors

Abstract: Nearly half of children experiencing cardiac arrest following cardiac surgery do not survive hospital discharge and patients who survive often experience significant neurological impairment. Additionally, increased resource utilization following cardiac arrest translates into adverse logistical and financial consequences. Although some studies have identified patient characteristics that increase the risk of cardiac arrest after pediatric cardiac surgery, modifiable risk factors, which could provide a foundati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
(90 reference statements)
0
3
0
Order By: Relevance
“…We summarized the POCA causes reported by cohort studies (Table 2). 1,2,[4][5][6]8,17,[21][22][23][24][25] We included risk factors in this summary; however, risk factors differ from causes, as a risk factor indicates an association, and association differs from causation. The summary demonstrated that the reported POCA risk factors and causes are abundantly diverse.…”
Section: Poca Causes Reported By Cohort Studiesmentioning
confidence: 99%
“…We summarized the POCA causes reported by cohort studies (Table 2). 1,2,[4][5][6]8,17,[21][22][23][24][25] We included risk factors in this summary; however, risk factors differ from causes, as a risk factor indicates an association, and association differs from causation. The summary demonstrated that the reported POCA risk factors and causes are abundantly diverse.…”
Section: Poca Causes Reported By Cohort Studiesmentioning
confidence: 99%
“…Nearly half of them do not survive hospital discharge, and the survivors often experience significant long-term neurodevelopmental disability (1, 2). Furthermore, the increased resource utilization following cardiac arrest presents logistical and financial challenges (3).…”
mentioning
confidence: 99%
“…In this issue of the World Journal for Pediatric and Congenital Heart Surgery , Riley and colleagues present the results of a scoping review to identify both modifiable and nonmodifiable risk factors associated with CA after pediatric cardiac surgery. 10 Their use of a scoping review format, instead of a systematic review, was appropriately chosen to allow for a more expansive overview of emerging evidence of varied risk factors and to identify knowledge gaps in this field of study. From the review of currently available literature, Riley et al identified 13 articles that met their inclusion criteria of studies evaluating CA in the postoperative period.…”
mentioning
confidence: 99%